Practice of the Caesarean Section in Four Maternities in Benin Using Robson Classification - HOUNKPATIN, BENJAMIN IGNACE B.; ABOUBAKAR, MOUFALILOU; DANGBEMEY, Djima Patrice (My University, 2020)
Objective: To measure for each of the ten (10) groups of women defined in Robson’s classification, the cesarean section rate, group size and its contribution to the overall cesarean section rate in four maternities in Benin. Methods: This was a retrospective study over a period of 3 years, from January 1, 2014 to December 31, 2016. Two workshops were organized for training in data collection and interpretation of results. Results: A total of 5442 files were included for the four health facilities during the study period. The overall cesarean section rate was 43.9%. The most represented group (30.3%) was multiparous women without scarred uterus, with a single term fetus, in cephalic presentation, and spontaneous labour (group 3). The largest contributor to the overall cesarean section rate was that of multiparous women with at least one uterine scar with a single fetus, eventually in cephalic presentation (group 5) with 29.5%. Conclusion: Caesarean section rates are high in groups of women with a favourable prognosis for vaginal delivery. It is also high in women with scarred uterus (group 5).
Keywords: Caesarean Section; Robson Classification; Benin